Variáveis cinemáticas espaço-temporais e angulares estão associadas ao consumo de oxigênio e aos limiares ventilatórios em corredores recreacionais? - Leite, Otávio Henrique Cardoso (2022)
Introduction: Over the years, the number of people who search to join the practice of running for physical conditioning or competitive performance is increasing. Running is an activity that requires a perfect interaction between physiological energy demand and muscle activity so that the body is able to transfer the forces generated by the response to movement. The increase in the number of running participants has stimulated the scientific community to analyze the association of different factors that can affect a runner's performance, such as the spatiotemporal and angular kinematic variables of the running, oxygen consumption and the ventilatory thresholds, which despite the relationship intuitive, the association between such variables is not clearly elucidated. Therefore, it is necessary to understand if physiological variables can be associated with biomechanical variables and if any of them can interfere in the performance of these athletes. Laboratory assessments such as exercise stress tests and kinematics assessment of running are commonly used and are able to identify changes in running parameters that interfere with the performance of recreational runners. Objective: To verify if there is an association between spatiotemporal and angular kinematics variables of the running with the oxygen consumption and the ventilatory thresholds of recreational runners during maximal incremental test on a treadmill associated with a three-dimensional biomechanical assessment of the running. Methods: This is a cross-sectional study with a sample of 40 recreational runners of both sexes. The runners were simultaneously submitted to a biomechanical analysis of the running and an ergospirometry during maximal incremental test on a treadmill. The spatiotemporal kinematic data and the angular data of the running obtained through the Movement Deviation Profile (MDP) were associated in a multivariate model of Bayesian structural equation searching association with oxygen consumption and ventilatory thresholds. Results: It was observed association of oxygen consumption with step frequence, step length and oscillation of the center of mass (r = 0.95), in addition to the association of step frequence with the first ventilatory threshold (OR = 1.03) and angular kinematics of the running obtained by the MDP with exhaustion (OR = 1.47). Conclusion: According to the findings of the present study, it can be concluded that step frequence is associated with the first ventilatory threshold; angular kinematic variables of running are associated with reaching exhaustion; higher step frequence and center of mass oscillation are associated with increased oxygen consumption and that increasing step length reduces oxygen consumption during the performance of a maximal incremental test on a treadmill.